Children’s Play Territorial: Understanding the Setting and Element - Fitria, Tika Ainunnisa (Universitas Aisyiyah Yogyakarta, 2024)
Territory is a form of occupation and behavior is related to social and cultural context. Understanding children's play territorial, through identifying 1) What children explore during playing in their neighborhood?. This question aims to find out how their their play area settings. 2) What are the element preferences when they play? Elements form the boundaries of children's play space. Territorial play is formed when children find elements around them. Elements automatically mark their ownership of the play space. Related to the setting, children are greatly influenced by the pattern and structure of space in their living environment. The relationship between children's play activities and the setting is clearly visible. This suggested that different play zones afford different experiences with nature, promoting ecological literacy amongst children in the kampung’s transitional space. Play territoriality is closely related to their movement in their environment.